COWORKER SUPPORT AND COMMUNICATION IMPACTING EMPLOYEE WORK DISCIPLINE THAT AFFECTS EMPLOYEE PERFORMANCE - Prameswari, Mutiara Chalinda; Evasari, Aprilia Dian (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH, 2023)
This research problem is limited to the variables of coworker support, communication, work discipline, and employee performance. The observed object is only within PT. Mitra Usaha Sukses Sejahtera. This research uses a quantitative approach that is useful for examining the population and samples within a company. Nonprobability sampling technique is used for sample selection. The research measurement tool utilizes a questionnaire as an instrument, which is then distributed to 35 respondents. The data obtained consists of respondent answers to the questions that were presented, and the source of this research is directly from the employees of PT. Mitra Usaha Sukses Sejahtera. The results of this research indicate that there is a significant direct influence of coworker support and communication on employee performance and there is a significant indirect influence of coworker support and communication on performance through work discipline .